USING LIGHT CLASSICAL MUSIC TO MAXIMIZE THE STUDENTS’ CAPABILITY TO RETAIN THE INFORMATION IN READING COMPREHENSION - Putu Ngurah Rusmawan (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2017)
The purpose of this paper is to describe an aids tool that can help the students tocomprehend, to retain the information, to understand, to improve the students‘ concentration in reading text for junior high school that is by using light classical music with appropriate volume, tempo, and right bit. This study is intended to describe the use of classical music to improve the students‘ concentration in reading text. This study used a descriptive qualitative study. This study is designing to describe the observed phenomenon in conducting teaching and learning process. The subject of the study was the junior high school English teacher‘s. The researcher used observation guidelines and note relating to design complete teaching and learning after the data has been collected, Light classical music can help the students relax. It affects students feeling therefore affect also in learning process. The right kind of light classical music tends to have both a relaxing and stimulating effect on the brain and on the whole nervous system. the students can absorb information much more quickly and effectively when student‘s brains are in a state of relaxed alertness